PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN LEVERAGE TERHADAP NILAI PERUSAHAAN - Pipit Putri Hariani (Intiqad: Jurnal Agama dan Pendidikan Islam, 2017)
Abstract The purpose of this research is to analyze the influence of corporate social responsibility and leverage on the value of the firm in Jakarta Islamic Index in the years 2013 – 2016. Population in this research are all companies (65 companies) that listed in Jakarta Islamic Index during years 2013 – 2016. Samples are taken by using purposive sampling method. I used 8 companies during 4 years starting 2013 – 2016, so total observation in this research are 32 observations. The using of analyzing method is by multiple regression linier simultaneously and partially with significant level 5%. The result of this research, show that the corporate social responsibility and leverage, influence value of the firm simultaneously. But only Leverage that significantly influence value of the firm partially. Meanwhile, Leverage influence but do not significantly value of the firm significanly in the companies listed Jakarta Islamic Index observation period in the years 2013 – 2016. Keywords: Corporate Social Responsibility, Leverage, Firm Value